Expletive there structures: a minimalist analysis - Ahmad Syafiq Amir Abdullah Zawawi; Fazal Mohamed Mohamed Sultan; Azhar Jaludin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Expletive structures can be recognized by the presence of there at the beginning of the sentence. Previous studies claim that there is not present through merge operations at the numeration level, but it enters into the syntax structure at the interface level of the Logical Form through Expletive Insertion Rules (EIR). There is a claim that there is no subject-to-subject movement in the expletive structure because there is generated directly to the subject position [Spec,TP]. Therefore, this study aims to re-evaluate this view and present an analysis based on morphosyntactic feature research. The data used in this study was taken from a corpus of three selected online novels based on the highest number of readers. The data type selected is the expletive construction of there only. The selected data is analyzed through the Minimalist Program (Chomsky, 2015). Through the corpus, this study found two expletive structures that are rarely discussed, namely BE-post-Expl and V-post-Expl. In vP Shell analysis, this study found that there is actually generated at the [Spec,vP] position due to the feature checking requirements [uExpl] brought by the small v node. However, subject-to-subject movement occurs when there moves to the subject position [Spec,TP] due to the need to check the feature [uExpl] assumed to be brought by the Tense. This proves that there is not generated at the Logical Form interface level, but rather there is a merge operation at the numeration level in the computational system. Thus, this study contributes to the understanding of the expletive structure based on morphosyntactic feature research.